Penerapan Pendekatan Open Ended Problems Dalam Meningkatkan Hasil Belajar Matematika Siswa Kelas V SD - Ervi Rahmadani (research, training and philanthropy institution Natural Aceh, 2020)
Abstract: The purpose of this research is to describe the implementation of open ended problems approach to improve mathematics learning outcomes in V grade 206 Ujung Baru Elementary School Districs Lilirilau, Soppeng. This research use a qualitative descriptive approach with cyclic classroom action research that includes planning, implementation, observation, and reflection. The focus of this research is the implementation and success of the open ended problems approach in mathematic teaching and learning process and also mathematics learning outcomes of the students class V. Subject in this research is V grade students in 206 Ujung Baru Elementary School totaling 10 students were active in the second semester of the school year 20015/2016. Data collection techniques in this research were the test, observation, and documentation. Data analysis techniques in this research were 1) data reduction, 2) data description, and 3) and deduction. The data in this research is the activities of teacher and students, and also students learning outcomes in mathematics subject. The result of this research shows the increase of the process and outcomes of mathematics learning in each cycle. The increasing of learning process and results can be seen from the 1” cycle to 2” cycle. Learning process and result 1” cycle is including sufficient qualification and then become better qualified on the 2” cycle. The conclusions of this research is the implementation of open ended problems approach can improve mathematic learning outcomes of the students class V 206. Abstrak: Tujuan penelitian ini adalah untuk mendeskripsikan penerapan pendekatan open ended problems dalam meningkatkan hasil belajar matematika siswa kelas V di SD Negeri 206 Ujung Baru Kecamatan Lilirilau Kabupaten Soppeng. Pendekatan penelitian ini adalah pendekatan deskriptif kualitatif dengan jenis penelitian tindakan kelas berdaur ulang/siklus yaitu meliputi perencanaan, pelaksanaan, observasi, dan refleksi. Fokus penelitian dalam penelitian ini adalah penerapan dan keberhasilan pendekatan open ended problems dalam proses belajar mengajar matematika serta hasil belajar matematika siswa kelas V. Subjek dalam penelitian ini adalah siswa kelas V SD Negeri 206 Ujung Baru Kecamatan Lilirilau Kabupaten Soppeng yang berjumlah 10 orang yang aktif pada semester genap tahun pelajaran 2015/2016. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah tes, observasi dan dokumentasi. Teknik analisis data dalam penelitian ini yaitu 1) mereduksi data, 2) mendeskripsikan data, dan 3) penarikan kesimpulan. Data penelitian ini adalah data aktivitas guru dan siswa serta hasil belajar siswa dalam pembelajaran matematika. Hasil penelitian menunjukkan adanya peningkatan proses dan hasil belajar matematika siswa pada setiap siklus. Peningkatan proses dan hasil belajar dapat dilihat dari siklus I ke siklus II. Proses dan hasil belajar siklus II termasuk kualifikasi cukup kemudian meningkat menjadi kualifikasi baik pada siklus II. Kesimpulan dalam penelitian ini adalah penerapan pendekatan open ended problems dapat meningkatkan hasil belajar matematika siswa kelas V SD Negeri 206.